Influence of Indonesian Army Information System Arrangement Concept in Realizing One Integrated, Fast, and Secure Data - Sahary, Fitry Taufiq; Mutaqin, Rizal; Mutaqin, Ghani; Nugroho, Fresy; Affandi, Azhar (PT. Riset Press International, 2025)
Bureaucratic Reform (RB) based on Presidential Decree Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform 2010-2025 in practice must be carried out by all Ministries/Institutions/Dinas/Institutions (K/L/D/I) in an innovative, creative and monitored manner institutional. The government also then issued Presidential Regulation Number 39 of 2019 concerning Data Management. Indonesia's One Data Policy (SDI) is expected to be a strategy for improving data governance to produce data that is accurate, up-to-date, integrated and accountable so that it can become the foundation for determining effective and appropriate policies. Indonesia's One Data Policy (SDI) is expected to be a strategy for improving management data to produce accurate, timely, integrated and accountable data which forms the basis for the creation of effective and targeted policies. The TNI AD Data Center is an Indonesian military facility that contains electronic systems and related components to be used and used for the placement, storage and processing of data in support of the Indonesian military information system. Data center facility infrastructure includes four aspects. First, infrastructure that guarantees the continuity of business processes when something critical and dangerous occurs in the data center. Internalization of RB, SPBE, and realizing SDI within the TNI AD institution must be realized through the arrangement of the Information System in order to further support the implementation of the Main Tasks of the TNI AD. The TNI AD needs to conceptually manage the data center, data processing architecture, network centralization, human resources, software and organizational management.